Use of sensory analysis recommendations for evaluation of organoleptic indicators of quality of goods - Belova, Tatyana; Porokhnya, Anna (My University, 2019)
The basic techniques of sensory analysis, which are used in the evaluation of organoleptic indicators of product quality, are considered. The main methods of product quality evaluation are described. It is emphasized the importance of carrying out an organoleptic assessment of both the quality of finished products and the raw materials from which they are made. For example, indicators are presented, which evaluated the quality of sugar biscuits. The advantages and disadvantages of sensory analysis are indicated.
Keywords: quality of production; quality of raw materials; sensory analysis; organoleptic parameters; якість продукції; якість сировини; сенсорний аналіз; органолептичні показники; кафедра маркетингу